Web Design Interaktif : Solusi Branding Digital English Corner Sijunjung - Naila Tri Tam; Denisha Aulya; Tri Wulan Agustin (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community service program aims to design and implement an interactive website for English Corner SJJ, a non-formal educational institution in Sijunjung. Although the institution has highly complete learning programs and adequate physical facilities—such as smart TVs and air-conditioned classrooms—it lacks a dedicated digital information platform to reach a wider audience. The service methodology comprises four stages: planning, wireframe design, system development using a content management system, and operational testing. The resulting outcome is an interactive, responsive website containing detailed profiles of the six learning programs, facilities, and a direct registration feature. In conclusion, this website serves as a strategic one-stop digital platform to enhance the institution's branding and efficiency in student recruitment.